Accretion of Fat-Free Mass Rather Than Fat Mass in Infancy Is Positively Associated with Linear Growth in Childhood. Issue 4 (11th April 2018) - Admassu, Bitiya; Ritz, Christian; Wells, Jonathan CK; Girma, Tsinuel; Andersen, Gregers S; Belachew, Tefera; Owino, Victor; Michaelsen, Kim F; Abera, Mubarek; Wibaek, Rasmus; Friis, Henrik; Kæstel, Pernille
Abstract: Background: We have previously shown that fat-free mass (FFM) at birth is associated with height at 2 y of age in Ethiopian children. However, to our knowledge, the relation between changes in body composition during early infancy and later linear growth has not been studied. Objective: This study examined the associations of early infancy fat mass (FM) and FFM accretion with linear growth from 1 to 5 y of age in Ethiopian children. Methods: In the infant Anthropometry and Body Composition (iABC) study, a prospective cohort study was carried out in children in Jimma, Ethiopia, followed from birth to 5 y of age. FM and FFM were measured ≤6 times from birth to 6 mo by using air-displacement plethysmography. Linear mixed-effects models were used to identify associations between standardized FM and FFM accretion rates during early infancy and linear growth from 1 to 5 y of age. Standardized accretion rates were obtained by dividing FM and FFM accretion by their respective SD. Results: FFM accretion from 0 to 6 mo of age was positively associated with length at 1 y (β = 0.64; 95% CI: 0.19, 1.09; P = 0.005) and linear growth from 1 to 5 y (β = 0.63; 95% CI: 0.19, 1.07; P = 0.005). The strongest association with FFM accretion was observed at 1 y. The association with linear growth from 1 to 5 y was mainly engendered by the 1-y association. FM accretion from 0 to 4 mo was positively associated with linear growth from 1 to 5 y (β = 0.45; 95% CI: 0.02, 0.88; P = 0.038) in the fully adjusted model. Conclusions: In Ethiopian children, FFM accretion was associated with linear growth at 1 y and no clear additional longitudinal effect from 1 to 5 y was observed. FM accretion showed a weak association from 1 to 5 y. This trial was registered at www.controlled-trials.com as ISRCTN46718296.